IDENTIFIKASI MOTIVASI INTRINSIK DAN EKSTRINSIK SISWA DAN HUBUNGANNYA TERHADAP HASIL BELAJAR MATA PELAJARAN BIOLOGI - Sri Rochani (LPMP Provinsi DKI Jakarta, 2023)
Student motivation is a factor in increasing student learning outcomes. However, the results of observations in class showed that students' motivation in Biology still needed to be improved. The research aims to identify students' intrinsic-extrinsic motivation and the relationship between motivation and learning outcomes. The research uses descriptive quantitative methods to explore student motivation. The research was conducted in class XII MIPA-4 MAN 14 Campus B Jakarta even semester of the 2022-2023 academic year. The motivation was identified using a questionnaire containing 12 questions. Participants in this study amounted to 28 students. The results of this study indicate that: 1) students tend to be intrinsically motivated as measured by the aspects of challenge, curiosity, mastery, assessment, and internal criteria. The average of the five aspects is above 2.5. 2) Students with scores above 2.5 or students with a tendency of intrinsic motivation have a higher correlation with learning outcomes in biology than students with a tendency of extrinsic motivation. This study concludes that by understanding the motivational tendencies of each student, teachers can direct students differently, which helps achieve student learning outcomes based on these motivational characteristics.